New Chitosan Polymer Scaffold Schiff Bases as Potential Cytotoxic Activity: Synthesis, Molecular Docking, and Physiochemical Characterization - Packialakshmi, Ponnusamy; Gobinath, Perumal; Ali, Daoud; Alarifi, Saud; Gurusamy, Raman; Idhayadhulla, Akbar; Surendrakumar, Radhakrishnan (Frontiers in Chemistry, 2022)
In this work, we synthesize the sulfonated Schiff bases of the chitosan derivatives 2a-2j without the use of a catalyst in two moderately straightforward steps with good yield within a short reaction time. The morphology and chemical structure of chitosan derivatives were investigated using FT-IR, NMR (1H—13C), XRD, and SEM. Furthermore, our chitosan derivatives were tested for their anticancer activity against the MCF-7 cancer cell line, and doxorubicin was used as a standard. In addition, the normal cell lines of the breast cancer cell MCF-10A, and of the lung cell MRC-5 were tested. Compound 2 h, with a GI50 value of 0.02 µM for MCF-7, is highly active compared with the standard doxorubicin and other compounds. The synthesized compounds 2a-2j exhibit low cytotoxicity, with IC50 > 100 μg/ml, against normal cell lines MCF-10A, MRC-5. We also provide the results of an in-silico study involving the Methoxsalen protein (1Z11). Compound 2h exhibits a higher binding affinity for 1Z11 protein (−5.9 kcal/mol) and a lower binding affinity for Doxorubicin (−5.3 kcal/mol) than certain other compounds. As a result of the aforementioned findings, the use of compound 2h has an anticancer drug will be researched in the future.